Sudden Cardiac Death—A New Insight Into Potentially Fatal Genetic Markers - Primorac, Dragan; Odak, Ljubica; Perić, Vitorio; Ćatić, Jasmina; Šikić, Jozica; Radeljić, Vjekoslav; Manola, Šime; Nussbaum, Robert; Vatta, Matteo; Aradhya, Swaroop; Sofrenović, Tanja; Matišić, Vid; et al. (Frontiers in Medicine, 2021)
Sudden cardiac death (SCD) is an unexpected and dramatic event. It draws special attention especially in young, seemingly healthy athletes. Our scientific paper is based on the death of a young, 23-year-old professional footballer, who died on the football field after a two-year history of heart disease. Based on the analysis of 294 genetic variants obtained by Invitae Corp. clinical laboratory test, as well as laboratory findings and ECG, the potential combination of fatal gene variants of the proband was reconstructed and presented as the possible cause of SCD by excluding other etiological factors including coronary artery disease and cardiomyopathy caused by de novo variant.